Reproductive rhythms, variation in operational sex ratio and sexual selection in crustaceans. Issue 3 (3rd July 2019) - Galipaud, Matthias; Baeza, J. Antonio; Dennenmoser, Stefan; Thiel, Martin
ABSTRACT: Operational sex ratio (OSR) has long been considered an important predictor of sexual selection strength. In crustaceans, OSR is primarily dependent upon reproductive rhythms. Herein, we model different conditions of reproductive rhythms to investigate the potential link between OSR and the strength of sexual selection, focusing on sexual traits commonly found in crustacean males. OSR can vary widely over a reproductive season as a result of reproductive rhythms, which limits the accuracy of its estimation based on a small sample. Overall, OSR was still predicted to correlate positively with sexual selection strength across different reproductive rhythms, yet only when males were assumed to experience a reproductive time-out. A review of experimental and field studies focusing on the link between OSR and sexual selection strength in crustaceans generally confirms our predictions. For the few studies failing to find the predicted pattern, we discuss potential causes for that discrepancy and urge future experimental research to specifically test for the effect of male time-out on the strength of sexual selection for male mating traits. Our model provides new predictions about the link between OSR and sexual selection and revives the long-lasting debate about OSR as an accurate estimate of sexual selection strength.